2003
DOI: 10.1021/jp036381v
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-Layer Films of Chitosan, Organophosphorus Hydrolase and Thioglycolic Acid-Capped CdSe Quantum Dots for the Detection of Paraoxon

Abstract: A polyelectrolyte architecture was fabricated that was composed of chitosan and organophosphorus hydrolase polycations along with thioglycolic acid-capped CdSe quantum dots (QDs) as the polyanion. This film was imaged by epifluorescence microscopy. UV−vis and emission spectroscopies were used to monitor the growth of the bilayer film due to the enhanced optical property of QDs. Photoluminescence of the functionalized QDs improved when sandwiched between the polycations layers. The presence of organophosphorus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
58
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 12 publications
0
58
0
Order By: Relevance
“…Organizing a large number of A, B, and C structures in a given area, 500 nm apart, provided a data storage system in which the information could be read by irradiation with blue (488 nm) and red (633 nm) lasers. [145,146] Using this approach the information density is limited by a) the area observable by the objective of the total internal reflection spectroscope, TIRS, b) the number of nanorods which manifest different scattering spectra in that observable area, and c) the number of distinctly resolvable resonance lines originating in the scattering spectra in the observable area. The far-field resolution of a microscope is roughly a 500 nm diameter circular area.…”
Section: Surface Plasmon Propagation Extraordinary Optical Transmissmentioning
confidence: 99%
“…Organizing a large number of A, B, and C structures in a given area, 500 nm apart, provided a data storage system in which the information could be read by irradiation with blue (488 nm) and red (633 nm) lasers. [145,146] Using this approach the information density is limited by a) the area observable by the objective of the total internal reflection spectroscope, TIRS, b) the number of nanorods which manifest different scattering spectra in that observable area, and c) the number of distinctly resolvable resonance lines originating in the scattering spectra in the observable area. The far-field resolution of a microscope is roughly a 500 nm diameter circular area.…”
Section: Surface Plasmon Propagation Extraordinary Optical Transmissmentioning
confidence: 99%
“…A linear growth mode was found in this study (R 2 5 0.97211), which agreed well with growth mode of Constantine's result about QDs-based LBL films. 23 The results indicated that almost the equal amounts of QDs were adsorbed after each deposition cycle. However, the emission peaks were slightly red shifted when increasing the coated bilayers on the fibrous mats.…”
Section: Fabrication Of Lbl Films Coated Cellulose Fibrous Matsmentioning
confidence: 96%
“…Therefore, electrospinning is a superior technique for creating luminescence thin films. However, many successful preparations of QDs/polymers by LBL, which were mostly based on quartz or spin-coating films as substrate, have been reported using QDs such as CdS-ZnS, 22 CdSe, 23 and CdTe. [24][25][26] There are sparse examples on the fabrication of luminescent electrospinning films using LBL.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their ease of preparation, high quantum yields (QYs), and tunable emissions in the visible range, CdSe and CdTe QDs are undoubtedly among the most promising materials used for the fabrication of fluorescent thin films. The techniques that are currently used for the construction of thin films-such as phase separation, [7] Langmuir-Schäfer deposition, [8] Langmuir-Blodgett transfer, [9] and layer-bylayer (LBL) assembly [10][11][12] -should also be useful for the fabrication of QD films. Of these approaches, LBL assembly using polyelectrolytes is one of the most efficient methods for fabricating thin films, mainly because of its low cost and simplicity, its independence of substrate size and topology, and the good mechanical and chemical stabilities of the resulting films.…”
mentioning
confidence: 99%
“…Of these approaches, LBL assembly using polyelectrolytes is one of the most efficient methods for fabricating thin films, mainly because of its low cost and simplicity, its independence of substrate size and topology, and the good mechanical and chemical stabilities of the resulting films. [10][11][12] For example, LEDs that emit a single color in the wavelength range 500-700 nm have been fabricated through LBL assembly of charged CdSe QDs with their oppositely charged polymers. [13,14] When used in conjunction with photolithography or electron-beam patterning, the LBL assembly technique can provide precise control over the deposition of QDs; these approaches have been applied to the fabrication of certain patterned QD films.…”
mentioning
confidence: 99%